(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
Тhe influence of nonprotein amino acids on branch chain amino acids aminotransferase of B. flavum and aromatic transaminase of C. freundii has been studied. According to the obtained results activity of both enzymes are inhibited by (S)-β-(N-benzylamino)alanine. The values of IC50 are 1.35 mM for the first enzyme and 3.8 mM for the last one. The mechanism of inhibition of these enzymes by (S)-β-(N-benzylamino)alanine was revealed. The data obtained suggested that branch chain amino acids aminotransferase is inhibited by (S)-β-(Nbenzylamino)alanine in mixed mode and aromatic transferase is inhibited in competitive mode of inhibition. The study of inhibition mechanisms is important for aminotransferases usage in improvement of amino acid production with strainproducers.